Review of the genus Diestramima Storozhenko, 1990 (Orthoptera: Rhaphidophoridae: Aemodogryllinae) from China - Zhu, Qi-Di; Shi, Fu-Ming (Zootaxa, 2018)
In this paper, 6 new species, 1 new subspecies and 1 newly recorded species of the genus Diestramima from China are described, i.e. Diestramima acutiapicis sp. nov., Diestramima bina sp. nov., Diestramima cycla sp. nov., Diestramima truncata sp. nov., Diestramima subtilis sp. nov., Diestramima eurya sp. nov., Diestramima austrosinensis quaterna ssp. nov. and Diestramima major Gorochov, 1998. The morphological photographs of these and 8 known species are provided. All specimens examined are preserved in the Museum of Hebei University.